Analisis Tantangan Dan Potensi Terhadap Produk Pakaian Bekas Impor/ Thrift - Sofa Fatihatun Nayiroh; Nabilla Lutfia; Syamsul Hidayat (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This research aims to analyze the challenges and potential of imported used clothing products. The research method in this research is to use qualitative methods. The population in this study were several students at Bina Bangsa University. The sampling technique used a random sampling technique by distributing questionnaires randomly. There were 55 respondents who were willing to fill out the questionnaire so that the sample used was 55 respondents. Based on the research results, it shows that challenges have an influence on imported used clothing products and potential has an influence on imported used clothing products and together the challenges and potential have an influence on imported clothing products.